Genetic polymorphisms in immune- and inflammation-associated genes and their association with bovine mastitis resistance/susceptibility - Khan, Muhammad Zahoor; Wang, Jingjun; Ma, Yulin; Chen, Tianyu; Ma, Mei; Ullah, Qudrat; Khan, Ibrar Muhammad; Khan, Adnan; Cao, Zhijun; Liu, Shuai (Frontiers in Immunology, 2023)
Bovine mastitis, the inflammation of the mammary gland, is one of the contagious diseases, which is characterized by chemical and physical changes in milk, and pathological changes in udder tissues. Moreover, depressed immunity and higher expression of inflammatory cytokines with an elevated level of milk somatic cell count are the key phenotypic traits that can be observed during mastitis. The usage of somatic cell count (SCC) and somatic cell score (SCS) as an indicator for the indirect selection of animals against mastitis resistance is widely in progress. However, very limited progress has been achieved so far in selecting mastitis resistance cows by using SCC and SCS as indicators because of their low heritability and environmental influence. Bovine mastitis being a quantitative trait is controlled by many genes. Thus recently, scientists have focussed on genetic markers associated with mastitis resistance phenotypic traits. Genomic selection has been launched to find genetically resistant animals to mastitis in a very early age. Different approaches such as genome-wide association studies, RNA-sequencing, microarray analysis and candidate gene methods are exercised to screen potential genetic markers associated with mastitis resistance. The candidate gene approach is widely used to screen genetically mastitis-resistant cows. Candidate gene approach by using the polymorphisms in immunity and inflammatory linked genes that were associated with mastitis resistance/ or susceptibility phenotypic traits (IL-6, interferon-gamma (IFN-γ), IL17, IL8 SCS and SCC) have been highlighted in the current review.